RESTRUKTURISASI PEMBIAYAAN DI MASA PANDEMI COVID-19 PADA PT. BANK SUMUT KCP SYARIAH KISARAN - Yunanda Dela; Tuti Anggraini ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2021)
he covid-19 pandemic has a significant impact on all aspects of human life, especially in the economic sector. In the banking sector, the existence of lockdown rules has preventedseveral business sectors from running, as a result it is difficult for business sectors that have loans from bank to repay loans. This study aims to fine out how toimplement financing restructuring during Covid-19 pandemic at PT. Bank Sumut KCP Syariah Kisaran. This Type of research is a qualitative research based on a descriptive approach. Techniques in data collection based on observation, interview and documentation. The analysis result shows taht the implementation of the financing restructuring at PT. Bank Sumut KCP Syariah Kisaran)